EACVI survey on burnout amongst cardiac imaging specialists during the 2019 coronavirus disease pandemic. (21st January 2022) - Joshi, Shruti S; Stankovic, Ivan; Demirkiran, Ahmet; Haugaa, Kristina; Maurovich-Horvat, Pal; Popescu, Bogdan A; Cosyns, Bernard; Edvardsen, Thor; Petersen, Steffen E; Carvalho, Ricardo Fontes; Cameli, Matteo; Dweck, Marc R
Abstract: Aims: The European Association of Cardiovascular Imaging Scientific Initiatives Committee conducted a global survey to evaluate the impact of the 2019 coronavirus disease (COVID-19) pandemic on the mental well-being of cardiac imaging specialists. Methods and results: In a prospective international survey performed between 23 July 2021 and 31 August 2021, we assessed the mental well-being of cardiac imaging specialists ∼18 months into the COVID-19 pandemic. One-hundred-and-twenty-five cardiac imaging specialists from 34 countries responded to the survey. More than half described feeling anxious during the pandemic, 34% felt melancholic, 27% felt fearful, and 23% respondents felt lonely. A quarter of respondents had increased their alcohol intake and more than half reported difficulties in sleeping. Two-thirds of respondents described worsening features of burnout during the past 18 months, 44% considered quitting their job. One in twenty respondents had experienced suicidal ideation during the pandemic. Despite these important issues, the majority of participants (57%) reported having no access to any formal mental health support at work. Conclusion: The survey has highlighted important issues regarding the mental well-being of cardiac imaging specialists during the COVID-19 pandemic. This is a major issue in our sub-specialty, which requires urgent action and prioritization so that we can improve the mental health of cardiovascular imaging specialists.